Biomineralization of Cd2+ and Pb2+ by sulfate-reducing bacteria Desulfovibrio desulfuricans and Desulfobulbus propionicus - Chen, Qianyanyu; Min, Qi; Wu, Hui; Zhang, Li; Si, Youbin (Frontiers in Environmental Science, 2025)
Sulfate reducing bacteria (SRB) is considered to be the most promising alternative biological treatment for immobilization of heavy metals due to its high efficiency and low cost. However, the mechanism underlying the biomineralization process has remained unclear. In this study, the kinetics and effects of Cd2+ and Pb2+ mineralization by sulfate-reducing bacteria Desulfovibrio desulfuricans and Desulfobulbus propionicus were investigated based on the microbial treatment technology, and the scanning electron microscope and energy dispersive spectroscopy (SEM-EDS), transmission electron microscope (TEM), X-ray diffractometer (XRD), Raman spectra and X-ray photoelectron spectroscopy (XPS), were used to reveal the mechanism of SRB treatment. The results showed that D. propionicus had a more efficient heavy metal mineralization rate than the D. desulfuricans, up to 98.97% and 75.62% at initial Cd2+ concentrations of 30 and 60 mg/L particularly. respectively. Both D. desulfuricans and D. propionicus had achieved 80% immobilization efficiency of Pb2+ with an initial Pb2+ concentration less than 50 mg/L. D. desulfuricans and D. propionicus facilitate the precipitation of Cd2+ and Pb2+ in the solution primarily as CdS, while Pb were mineralized and removed through phosphate and oxide precipitates of Pb and PbS via their metabolic activities involving sulfate conversion. This research suggested that mineralization of heavy metals mediated by microbial sulfate reduction should have prospects for broad application in bioremediation of mine drainage.